PELAKSANAAN PERLINDUNGAN SATWA LANGKA BERDASARKAN UNDANG-UNDANG NOMOR 5 TAHUN 1990 TENTANG KONSERVASI SUMBER DAYA ALAM HAYATI DAN EKOSISTEMNYA (STUDI DI SEKSI KONSERVASI WILAYAH I SURAKARTA BALAI KONSERVASI SUMBER DAYA ALAM JAWA TENGAH) - Fakultas Hukum Universitas Sebelas Maret Surakarta, Arief Budiman (MAJALAH ILMIAH GEMA, 2014)
Illegal wildlife trade is a serious threat to the conservation of wildlife in Indonesia. Wildlife illegally traded based on the facts found in the field are mostly caught from the wild, instead of breeding. Natural Resources Conservation Center as an institution that has an important role in rescue efforts are strategic and Endangered species protection of law number 5 of 1990 on Conservation of Biological Resources and Ecosystems This study to determine how the efforts of the Conservation Section of Region I Surakarta Agency conservation of natural resources in Central Java in the protection of endangered species in the region and the challenges faced every obstacle In overall role of the Natural Resources Conservation Center has been running well but there is still a shortage of human resources and lack of infrastructure to support the performance. Key words: The implementation, Conservation, endangered species protection